Analisis Dampak Insentif Fiskal Perpajakan Mobil Listrik Berbasis Baterai di Indonesia - Firdiansyah, Akhmad; Gultom, Yulifar Amin (JURNAL PAJAK INDONESIA, 2023)
The acceleration of the battery-based electric vehicle program will soon be realized in Indonesia considering the concerns about the impact of carbon pollution and global warming, the government's role in making fiscal policies in the form of tax incentives has been made, but it is necessary to carry out an in-depth analysis of the impacts, this research aims to carry out analysis of the impact on tax fiscal policy incentives given to the battery-based electric vehicle industry in Indonesia with an emphasis on battery procurement for national electric vehicles. The analysis approach uses descriptive quantitative methods with the CGE-GTAP analysis tool. The results of this research state that eliminating import duties has a positive effect only on increasing exports and increasing production in all sectors (including electric vehicles) except the EVBattery sector. For other economic components, negative changes can be seen. This shows that the elimination of import duties for batteries failed to encourage the competitiveness of domestic battery production and the terms of trade decreased. The incentive to eliminate import duties accompanied by VAT shows a proxy for domestic and foreign economic policy. Even though it failed to increase GDP, the competitiveness of the battery and vehicle sector, which is the main focus of this research, experienced increased production and increased domestic demand, decreased imports and increased exports. This condition of increasing competitiveness encourages an increase in welfare (equivalent variation).